TCP Versus TFRC over Wired and Wireless Internet Scenarios: An Experimental Evaluation - Luca De Cicco; Saverio Mascolo; Yevgeni Koucheryavy; Jarmo Harju; Villy Iversen (Next Generation Teletraffic and Wired/Wireless Advanced Networking, 2006)
TCP NewReno is the standard transport protocol originally designed to transport bulk data over the Internet. During the years it has been very successful to provide Internet stability due to its congestion control scheme. However TCP is not very suitable for multimedia streaming applications, that are time sensitive, because of its retransmission and multiplicative decrease mechanisms. The alternative to TCP is the User Datagram Protocol (UDP) which works as a simple packet multiplexer/demultiplexer and does not implement any congestion control scheme or retransmission mechanism. However, it has been pointed out that applications that don’t use congestion control schemes are dangerous for the stability of the Internet [1]. The TCP Friendly Rate Control (TFRC) is currently been discussed within the IETF as a possible leading standard for streaming multimedia flows. This paper aims at investigating the performances of TCP and TFRC congestion control schemes in wired public Internet and in mixed wired/wireless Internet using a commercial UMTS card. The experiments carried out have shown that TFRC exhibits smoother rate dynamics in all wired scenarios, whereas in the case of UMTS scenario its burstiness is comparable to that of TCP.